1998
DOI: 10.1148/radiology.206.3.9494479
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and effects of extravasation of ionic and nonionic CT contrast media during rapid bolus injection.

Abstract: The frequency of extravasation of contrast medium after mechanical bolus injection is higher than that reported for hand-injection or drip-infusion techniques, but there is no correlation between injection rate and extravasation frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
5
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 0 publications
11
79
5
8
Order By: Relevance
“…Most extravasations involve small volumes of less than 10 ml, evolving without complications; however, large volumes of 50 ml or more can damage neighboring tissues of the puncture site and, rarely, compartmental syndrome (6) . According to international literature (2,(8)(9)(10) , the frequency of radiopaque medium extravasation varies between 0.3% and 3.6%. Next, in the results section, findings related to extravasation of the radiopaque medium were described separately, as this is a local adverse effect for which different sample subject inclusion and exclusion criteria were adopted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Most extravasations involve small volumes of less than 10 ml, evolving without complications; however, large volumes of 50 ml or more can damage neighboring tissues of the puncture site and, rarely, compartmental syndrome (6) . According to international literature (2,(8)(9)(10) , the frequency of radiopaque medium extravasation varies between 0.3% and 3.6%. Next, in the results section, findings related to extravasation of the radiopaque medium were described separately, as this is a local adverse effect for which different sample subject inclusion and exclusion criteria were adopted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature (2,(8)(9)(10) about the occurrence of extravasation refers to research that used some criteria different from those used in this study, such as the exclusive use of plastic catheters, exclusive use of automatic injection and different criteria to select the research subjects. In comparing the results of this study with international references, attempts were made to adapt results from the HCPA to the criteria used by different researchers, as shown in Table 2.…”
Section: Radiopaque Medium Extravasationmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation of reflux from the injection route has been reported as a safety countermeasure during power injection [3,[9][10][11]. In some reports, the saline test injection was performed manually [2,3,12].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of extravasation from contrast medium injection with a power injector increased with an increase in injection pressure. Regarding the risk of extravasation, it has been reported that there was no correlation between the injection rate and the extravasation rate or comprehensive reactions [6,10]. Amaral et al reported that extravasation was related to a high injection rates and pressures, regardless of the location, size, or type of catheter.…”
Section: Discussionmentioning
confidence: 99%